Postnatal levels of glycated albumin and glycated hemoglobin A1c in mothers of large-for-gestational-age newborns - Mojca Železnik; Alenka Trampuš Bakija; Darja Paro-Panjan; Darja Paro-Panjan; Aneta Soltirovska-Šalamon; Aneta Soltirovska-Šalamon (Frontiers in Pediatrics)
BackgroundGestational diabetes mellitus (GDM) is an important cause of macrosomia. The value of glycated albumin (GlyA) has been demonstrated to be a useful marker of glycemic control in pregnancy and a predictor of adverse perinatal outcomes. The aim of this study was to investigate the relationship between the postnatal levels of GlyA and glycated hemoglobin A1c (HbA1c) regarding the prenatal diagnosis of GDM in mothers of large-for-gestational-age (LGA) newborns.MethodsThe study included mothers and their LGA newborns born between July 2017 and September 2019. The mothers were grouped according to the prenatal diagnosis of GDM, and measurements of GlyA and HbA1c levels in their serum were performed on the first day after delivery of a LGA newborn.ResultsA total of 61 LGA newborns and their mothers were enrolled in the study. The median GlyA level was higher, at 16.4% (81.0 µmol/L), whereas the HbA1c level was lower in the group without a prenatal diagnosis of GDM; the differences between groups regarding the GlyA and HbA1c levels were not significant (p > 0.05). The postnatal level of maternal GlyA was positively correlated with birth weight (β = 0.022, p = 0.007), but no correlation with the presence of other adverse perinatal outcomes was found.ConclusionMothers of LGA newborns who were not diagnosed with GDM during pregnancy had higher median levels of GlyA and lower HbA1c levels than mothers with prenatal diagnosis of GDM. Values of GlyA in mothers were positively correlated with the birth weight of their newborns but no correlation with other adverse perinatal outcomes was found. Our results indicate the potential value of GlyA for screening of GDM in the last trimester of pregnancy.